Avaliação de uma composição musical para melhorar a qualidade de sono de pessoas idosas com insônia - Hatem, Samir Longoni (2019)
The aim of this study was to evaluate the effectiveness of a song composed for improving sleep in elderly people with insomnia. The study is a nonblind open randomized clinical trial. To verify the efficiency of the music, the sample was divided into two groups. The intervention group tested the music composed for this purpose; The control group used two compositions by Mozart. The sample consisted of 11 elderly people diagnosed with chronic insomnia, aged 60 years or older, randomly drawn, and five elderly participated in the intervention group and the others in the control group. Elderly people who use sleeping medication or who were diagnosed with other sleep disorders besides insomnia were excluded from the study. Sleep quality was assessed using the Pittsburg Sleep Quality Index, an instrument validated in Portuguese. Data were presented as mean and standard deviation, median and interquartile ranges. Quantitative data were analyzed with Student's t-test for independent and paired samples. The answer of the study was the efficiency of the composite composition for research against a Mozart selection as a reference. Pittsburg scale mean scores decreased for both groups. When comparing intergroups the differences found were not statistically significant. When intra-groups were compared, the mean Pittsburg scale scores showed statistically significant differences for the intervention group (p = 0.003). The main findings indicate that the withdrawal of participating in the research by some elderly people was due to the fact that they realize that they do not like to sleep with music. Sleep quality improved for both groups. The composite music performed better.